Analysis of significantly mutated genes as a clinical tool for the diagnosis in a case of lung cancer. (2017) - Miyashita, Yoshihiro; Hirotsu, Yosuke; Tsutsui, Toshiharu; Higashi, Seishi; Sogami, Yusuke; Kakizaki, Yumiko; Goto, Taichiro; Amemiya, Kenji; Oyama, Toshio; Omata, Masao
Abstract: Bronchoendoscopic examination is not necessarily comfortable procedure and limited by its sensitivity, depending on the location and size of the tumor lesion. Patients with a non-diagnostic bronchoendoscopic examination often undergo further invasive examinations. Non-invasive diagnostic tool of lung cancer is desired. A 72-year-old man had a 3.0 cm × 2.5 cm mass lesion in the segment B1 of right lung. Cytological examination of sputum, bronchial washing and curetted samples were all "negative". We could confirm a diagnosis of lung cancer after right upper lung lobe resection pathologically, and also obtained concordant results by genomic analysis using cytological negative samples from airways collected before operation. Genetic analysis showed mutational profiles of both resected specimens and samples from airways were identical. These data clearly indicated the next generation sequencing (NGS) may yield a diagnostic tool to conduct "precision medicine".